BISCATINHA: A DECOLONIAL VISION ABOUT THE MARGINALITY IMPOSED ON GIRLS WITHIN THE SCHOOL CONTEXT - Magnani Delle Piagge, Ana Claudia [UNESP]; Souza, Tatiane Pereira de (Unesp-faculdade Ciencias & Letras, 2020)
This article aims to address the discussion of gender in the school routine regarding the treatment of girls and women in society. The methodology used was bibliographic research supported by decolonial authors, cultural studies of ethno-racial and gender diversity in the human and social sciences, as well as on-site observation of school routine. In this sense, we understand that the girl's body, inside the school, has been educated, conformed, dehumanized to justify an imposing model of standards of behavior and normative thinking in society, a fact that collaborates with our understanding of the urgency to promote more discussions about this theme.
Keywords: Education; Genre; Women/girls; Critical thinking